2017
DOI: 10.4314/tjpr.v16i9.2
|View full text |Cite
|
Sign up to set email alerts
|

Erratum for “Lycium barbarum polysaccharide attenuates cisplatin-induced apoptosis in ovary granulosa cells via alleviation of endoplasmic reticulum stress”

Abstract: ErratumJin et al Trop J Pharm Res 2017, 16(4): 827-835 http://dx.doi.org/10.4314/tjpr.v16i4.12The information under Acknowledgement section should be "None". Abstract line11: "Bcl-2 and Bax" should be changed to "Bcl-2/Bax" Abstract: "p>0.05" should be changed to "p<0.05" wherever it occurred. Citation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Various studies have identified correlations between supplementation of polysaccharides and protective roles in ovary‐related disorders, such as PCOS and ovarian cancer (Guo et al, 2020; Zhang et al, 2020). For example, Lycium barbarum polysaccharide was revealed to suppress apoptosis of cisplatin‐stimulated rat GCs in a dose‐independent manner and significantly downregulate expression of glucose‐regulated protein 78 kDa and CHOP, thereby confirming a protective effect via regulation of ER stress (Huang et al, 2018). Another study reported that polysaccharides from Dendrobium nobile Lindl.…”
Section: Natural Products and Bioactive Ingredients Of Tcm Inhibit Ap...mentioning
confidence: 96%
“…Various studies have identified correlations between supplementation of polysaccharides and protective roles in ovary‐related disorders, such as PCOS and ovarian cancer (Guo et al, 2020; Zhang et al, 2020). For example, Lycium barbarum polysaccharide was revealed to suppress apoptosis of cisplatin‐stimulated rat GCs in a dose‐independent manner and significantly downregulate expression of glucose‐regulated protein 78 kDa and CHOP, thereby confirming a protective effect via regulation of ER stress (Huang et al, 2018). Another study reported that polysaccharides from Dendrobium nobile Lindl.…”
Section: Natural Products and Bioactive Ingredients Of Tcm Inhibit Ap...mentioning
confidence: 96%